Gambaran managemen diri dan dukungan keluarga pasien diabetes mellitus - SAKITRI, GANIK; Kholifah Hasnah (Intan Husada : Jurnal Ilmiah Keperawatan, 2023)
DM patient self-management is an action taken by DM patients to manage and control DM which includes activity, diet, exercise, monitoring blood sugar, drug control and foot care. The goal of self-management is to optimize metabolic control in the body, prevent acute and chronic complications, optimize the patient's quality of life and reduce costs incurred for the treatment of DM. This research was conducted to find an overview of self-management of diabetes mellitus patients and family support. The sample in this study were 34 respondents. The instruments used were self-management and family support questionnaires. Data is processed with univariate. The results of research on self-management as a whole as much as 58.8% are in the high category. The results of the study regarding the description of high family support were as much as 79.4%. Conclusion This study shows that most of the respondents have good self-management both in terms of aspects of diet, medication, monitoring blood sugar levels, activities and foot care. The results of the study also provide an overview of family support for diabetes mellitus patients in the good category.